Aerogel insulation in building energy retrofit. Performance testing and cost analysis on a case study in Rome. (December 2020) - Orsini, Federico; Marrone, Paola; Asdrubali, Francesco; Roncone, Marta; Grazieschi, Gianluca
Abstract: Green Houses Gases (GHG) are negatively influencing the climate, increasing the Global Warming (GW) of the planet. Improving the energy performance of buildings is one of the main strategies that have to be adopted as soon as possible. In this contest, "Super Insulation Materials" (SIM) have been recently developed. The paper fits into this framework and investigates the aerogel applications in architecture to enhance energy retrofitting processes, evaluating its performances and economic feasibility. The study identifies different technological scenarios and analyzes their performance and cost application, highlighting the potential (i.e. saving of usable area inside up to 500% comparing with traditional insulators) and the limits of the aerogel (mean global cost that is 45% higher) application as a technological system for the reduction of energy consumption.